Intravenous iron sucrose when administered to moderately anemic pregnant women raises the hemoglobin concentration and replenishes body iron at 6 months - Pritam Halder; Shashi Kant; Archana Singh; Ravneet Kaur (Journal of Family Medicine and Primary Care)
Introduction: Intravenous iron sucrose (IVIS) is a rapidly acting, safe, and effective treatment for moderate anemia among pregnant women. The effectiveness of IVIS at 6 months post IVIS infusion was unknown. We, therefore, assessed the mean increase in hemoglobin concentration and body iron replenishment status at 6 months after the last dose of IVIS infusion. Methods: The study was conducted in 28 villages served by two primary health centers in district Faridabad, Haryana. The participants (n = 129), when originally recruited in 2020, were all moderately anemic (hemoglobin level 7.0 to 9.9 g/dL) pregnant women in either the second or third trimester of pregnancy. Their iron deficiency was calculated by Ganzoni’s formula with additional allowance of 500 mg of depot iron. The calculated deficit was rounded off to the nearest 100 mg. The dose of IVIS was 300 mg of iron diluted in 300 ml of normal saline administered intravenously every third day till the full calculated dose was administered. In this study, we collected the follow-up blood specimen 6 months after the last dose of IVIS and measured the hemoglobin concentration, C-Reactive protein (CRP), and serum ferritin level. Hemoglobin concentration was measured using an automated hematology analyzer (Sysmex XS-1000i). Serum ferritin and CRP were measured by enhanced chemiluminescence immunoassay and the enzymatic heterogeneous, sandwich immunoassay method, respectively (VITROS ECiQ, Ortho Clinical Diagnostics, New Jersey, USA). Results: The mean [standard deviation (SD)] duration of time elapsed since the administration of the last dose of IVIS infusion was 6.4 (0.9) months. The mean (SD) hemoglobin level at the time of original recruitment (baseline) was 8.7 ± 0.8 g/dL. The mean (SD) increase in the hemoglobin concentration at 6 months follow-up was 3.2 [95% confidence interval (CI): 3.0–3.4)] g/dL. The median [interquartile range (IQR)] serum ferritin level (ng/mL) at follow-up was 28.1 (12.7, 61.5). A total of 10.2% of the participants had a raised (>10 mg/L) CRP level. Adjusting for CRP level and based on serum ferritin level, the proportion of participants who were iron-deficient was 35.3%. The proportion of participants who had any degree of anemia was 70.5%. Conclusion: Administration of IVIS infusion was effective in raising the mean hemoglobin concentration and in replenishing the body iron reserve at 6 months post infusion.